2023
DOI: 10.3390/v15051030
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Transmission of HIV-1 and HIV-2 from Infected Macrophages and Dendritic Cells to CD4+ T Lymphocytes

Abstract: Macrophages (Mø) and dendritic cells (DCs) are key players in human immunodeficiency virus (HIV) infection and pathogenesis. They are essential for the spread of HIV to CD4+ T lymphocytes (TCD4+) during acute infection. In addition, they constitute a persistently infected reservoir in which viral production is maintained for long periods of time during chronic infection. Defining how HIV interacts with these cells remains a critical area of research to elucidate the pathogenic mechanisms of acute spread and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…[40] The macrophage-led spleen in ammatory status, as seen in one non-HIV infected patient, [41] may release signs of transactivation of proviruses infected CD4 + driven by the innate immune response to viscerotropic Leishmania, allowing viral replication and inducing infected and bystander T-cells apoptosis and pyroptosis. [20,53] Interestingly, while non-HIV VL shows a high level of IL-6-driven acute phase response, a cytokine linked to severe VL without HIV, [24,57] its marker, Creactive protein [58] was near normal among our coinfected patients, reinforcing the idea that instead of IL-6, it was IL-1a released by pyroptotic cells the leading cause of immunological failure of our coinfected patients.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…[40] The macrophage-led spleen in ammatory status, as seen in one non-HIV infected patient, [41] may release signs of transactivation of proviruses infected CD4 + driven by the innate immune response to viscerotropic Leishmania, allowing viral replication and inducing infected and bystander T-cells apoptosis and pyroptosis. [20,53] Interestingly, while non-HIV VL shows a high level of IL-6-driven acute phase response, a cytokine linked to severe VL without HIV, [24,57] its marker, Creactive protein [58] was near normal among our coinfected patients, reinforcing the idea that instead of IL-6, it was IL-1a released by pyroptotic cells the leading cause of immunological failure of our coinfected patients.…”
Section: Discussionmentioning
confidence: 61%
“…[20,22] However, this mechanism of CD4 + loss appears minimal as compared to virologic failure, when HIV infection is productive. [51] A similar mechanism may have been through macrophages, since HIVinfected macrophages are able to transmit cell-free or quiescent HIV provirus to CD4+, as observed [52][53][54][55] and therefore contributing to its activation and depletion. This hypothesis will be investigated in our patients' stored samples.…”
Section: Discussionmentioning
confidence: 91%
“…[52][53][54][55][56] Recently, several reports have demonstrated that cell-to-cell transmission (i.e., proximal cell) is the primary mode of infection spread, accounting for approximately 60% of viral transmission, 57,58 revealing one clear advantage of cell-to-cell transmission: it appears to be unaffected by most cellular barriers, allowing for more efficient infection of target cells when in close contact with donor-infected cells, as recently demonstrated for HIV-1 and HIV-2 primary isolates. 59 One of these studies also showed that cell-to-cell transmission during treatment is less sensitive to drugs than cell-free infection. 60 However, these results are still controversial and further research is needed to better understand the mechanisms underlying cell-to-cell transmission.…”
Section: Hiv Transfer To Target Cellsmentioning
confidence: 99%
“…Macrophages and monocytes may play a role in spreading the viral infection to lymphocytes during reservoir formation and viral blips. 34 , 35 , 36 , 37 , 38 , 39 In the last decades, many groups have worked to decipher the mechanism behind HIV latency in the aforementioned resident immune cells but mainly focused on peripheral CD4 + T cells. Diverse mechanisms were addressed that may be responsible for HIV latency, such as the epigenetic and non-epigenetic regulation of HIV latency.…”
Section: Hiv Transcription Integrated Stress Response and Hiv Latencymentioning
confidence: 99%